Pengaruh SOP dan Sarana Prasarana terhadap Efektivitas Layanan Wajib Lapor Klien Dewasa PB di Balai Pemasyarakatan Kelas 1 Jambi - Bella Debora; Yenny Yuniarti; Fitri Widiastuti (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
This study aims to determine the influence of Standard Operating Procedures (SOP) and Facilities and Infrastructure, both partially and simultaneously, on the Effectiveness of Public Services for adult parole clients at Balai Pemasyarakatan (Bapas) Class I Jambi. The research employs a quantitative method with a descriptive approach to systematically and measurably describe the relationships among variables. Data were collected through questionnaires distributed to 90 respondents selected using the simple random sampling technique, ensuring equal opportunities for all participants to be included in the sample. The data were analyzed using multiple linear regression analysis to test the effect of each variable on service effectiveness. The findings reveal that both partially and simultaneously, SOP and Facilities and Infrastructure have a positive and significant effect on the effectiveness of public services. Among the two variables, Facilities and Infrastructure exert a more dominant influence, highlighting the importance of adequate resources in improving service quality. Meanwhile, the implementation of SOPs needs to be further optimized to make a more substantial contribution to enhancing the effectiveness of public service delivery for adult parole clients at Bapas Class I Jambi.